Personal tax computation by microcomputer / Siti Salwah Salim and Ong Gim Yan - Salim, Siti Salwah; Ong, Gim Yan (Universiti Teknologi MARA Cawangan Pahang, 1992)
The overview objective of this paper is to present a microcomputer-based tools in helping public in their own tax computation. This in time will help the hectic assessment work in the Inland Revenue and for collection purposes. Written in Turbo Pascal Version 6.0 and implemented on an IBM PC.